Numerical effectiveness of different formulations of the rigid finite element method - Adamiec-Wójcik, Iwona; Drąg, Łukasz; Wojciech, Stanisław (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents an application of different formulations of the rigid finite element method (RFEM) to dynamic analysis of flexible beams. We discuss numerical effectiveness of the classical RFEM and an alternative approach in which continuity of displacements is preserved by means of constraint equations. The analysis is carried out for a benchmark problem of the spin-up motion in planar and spatial cases. Torsion is omitted for numerical simulations and two cases of the new approach are considered. The results obtained by means of these methods are compared with the results obtained using a nonlinear two-node superelement.
Keywords: flexibility of links; rigid finite element method; dynamic analysis; nonlinear motion; numerical effectiveness